2016
DOI: 10.1021/acsbiomaterials.6b00133
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Dissolution Rate of Wear Debris from Silicon Nitride Coatings

Abstract: Silicon nitride (SiN x ) coatings have recently been introduced as a potential material for joint implant bearing surfaces, but there is no data on wear debris morphology nor their dissolution rate, something that could play a central role to implant longevity. In this study, wear debris was generated in a ball-ondisc setup in simulated body fluid. After serum digestion the debris was analysed with scanning electron microscopy and energy-dispersive x-ray spectroscopy. The particle dissolution rate was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…This may be due to variation between particle generation experiments. The model Si 3 N 4 particles used were similar in size to recently published data on nanoscale Si 3 N 4 debris produced by a coating applied to a CoCrMo substrate [47], though particles up to a few microns in size were also identified by [47]. The nanoscale silicon nitride particles were also spherical and existed as aggregates of a similar size to those observed in the current study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This may be due to variation between particle generation experiments. The model Si 3 N 4 particles used were similar in size to recently published data on nanoscale Si 3 N 4 debris produced by a coating applied to a CoCrMo substrate [47], though particles up to a few microns in size were also identified by [47]. The nanoscale silicon nitride particles were also spherical and existed as aggregates of a similar size to those observed in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…Spherical nanoparticles with a circularity of greater than 0.7, when taken up by cells, may have different biological effects than less spherical particles, since particles with rough edges may break through endosomal or lysosomal membranes and thus reside more frequently in cytoplasm [51]. Measuring particle parameters also allows detection of particle dissolution; our results suggest that Si 3 N 4 particles may dissolve less quickly in vivo than has been previously suggested by simulations of in vivo conditions [47], since there were no detectable changes to particle size or shape. Additionally, results suggest that corrosion of particles, which may occur within macrophages, did not affect a significant number of particles within the given time frame.…”
Section: Discussionmentioning
confidence: 59%
“…This type of coating has previously shown promising properties in terms of high biocompatibility, hardness, and low wear rates [17][18][19][20]. A further possible advantage of this coating compared to other ceramic coatings is its slow solubility in aqueous solutions [21,22], in combination with the high biocompatibility of its wear particles and ions [23]. We seek to develop SiN x coatings that dissolve controllably and generate wear particles of a higher dissolution rate than the coating itself (due to the higher surface area), and whose dissolution also gives biocompatible ions.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Recently, there has been a growing interest for amorphous silicon nitride (SiN x ) coatings for metallic medical implants, in contrast to fully ceramic Si 3 N 4 implants. [4][5][6][7][8][9] The use of a ceramic coating on a metallic implant would combine the ductility of the metallic implant with the biocompatibility of the ceramic, without the risk of a catastrophic failure of a fully ceramic implant. [8] It has been shown that a SiN x coating can reduce implant corrosion and limit the metal ion release from metallic implants, thus reducing harmful inflammation in the surrounding tissue.…”
Section: Silicon Nitridementioning
confidence: 99%
“…[8] In addition to the favorable mechanical properties, such as high wear-resistance, SiN x wear debris is soluble in aqueous solutions, further reducing the risk of undesired reactions between the host and the implant. [9][10][11] 1.2 Silicon nitride and silicon nitride-based materials 3…”
Section: Silicon Nitridementioning
confidence: 99%